2008
DOI: 10.1177/153303460800700406
|View full text |Cite
|
Sign up to set email alerts
|

The Performance of 17-gauge Cryoprobes In Vitro

Abstract: In cryosurgery it is crucial that the performance of cryoprobes is predictable and constant. In this study we tested the intra- and interneedle variation between 17-gauge cryoprobes in two homogeneous mediums. Also, a multiprobe setup was tested. Cryoprobe performance was defined as the time it takes one cryoprobe to lower the temperature from 0 to -20 degrees C as measured by four thermosensors each at 3 mm distance from the cryoprobe. In agar eight cryoprobes were tested during six freeze cycles, and in gel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
(1 reference statement)
0
3
0
Order By: Relevance
“…These ultrathin cryoprobes are easily introduced into the kidney, minimize bleeding from the puncture tract and reduce the risk of renal fracture [3]. Although different ice ball sizes are available, the ablation zone achieved is smaller and therefore multiple cryoprobes [4], acting synergistically, need to be inserted [5]. The clinical safety of ultrathin cryoprobes is proven [6] but concerns about their efficacy might still exist.…”
Section: Introductionmentioning
confidence: 99%
“…These ultrathin cryoprobes are easily introduced into the kidney, minimize bleeding from the puncture tract and reduce the risk of renal fracture [3]. Although different ice ball sizes are available, the ablation zone achieved is smaller and therefore multiple cryoprobes [4], acting synergistically, need to be inserted [5]. The clinical safety of ultrathin cryoprobes is proven [6] but concerns about their efficacy might still exist.…”
Section: Introductionmentioning
confidence: 99%
“…Beemster et al 19 found the performance of 17-gauge cryoprobes was less variable in a multiple probe configuration than a single cryoprobe when the temperature was measured 3 mm from the cryoprobe in agar and gel. In that study, the average temperature variation was 3.8°C greater in the multiple probe group.…”
Section: Commentmentioning
confidence: 99%
“…The flow of 37°C blood within or adjacent to the cryoablated region may lead to heat dissipation by the ''heat sink effect'' and complicate attainment of requisite freeze temperatures for the appropriate duration. 20,21 Multipoint thermal sensor (MTS) needles allow accurate and reproducible temperature determination across multiple points along the needle, 22 providing the surgeon a direct means to ascertain CA temperatures within the area of the RCN. Utilizing MTS needles can help overcome differences in renal tumor microanatomy and vascular distribution, and inform cryoprobe placement and freeze times, hypothetically decreasing the risk of incomplete ablation.…”
Section: Introductionmentioning
confidence: 99%